Negative plate, lithium ion battery and electric equipment

By designing a multi-layer structure in the negative electrode sheet of a lithium-ion battery, combining silicon carbon, graphite and hard carbon materials, the volume expansion, low-temperature performance and corner lithium analysis of silicon carbon materials during circulation are solved, and the comprehensive effects of high energy density, fast charging performance and low expansion are achieved.

CN119581485AActive Publication Date: 2025-03-07ZHEJIANG LIWINON ELECTRONIC TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411549291.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

The existing lithium-ion battery negative electrode material, silicon carbon, expands in large volume, poor low-temperature performance, and severe corner lithium analysis during the cycle, making it difficult to meet the requirements of high energy density, fast charging performance and low expansion at the same time.

Method used

A negative electrode sheet is designed, by sequentially providing a negative electrode current collector layer, a first negative electrode active material layer and a second negative electrode active material layer, the first negative electrode active material layer includes silicon carbon, first graphite and first hard carbon, and the second negative electrode active material layer includes second graphite and second hard carbon. The layer spacing and structure of the hard carbon are conducive to the embedding and detachment of lithium ions, reducing expansion and improving kinetics.

Benefits of technology

It significantly suppresses the volume expansion problem of silicon carbon, improves the overall pressure density and low temperature performance, improves the dynamic performance of the battery cell, reduces the corner lithium analysis phenomenon, and improves the charging capacity of the battery cell while ensuring high energy density.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005114641050000061
    Figure BDA0005114641050000061
  • Figure BDA0005114641050000071
    Figure BDA0005114641050000071
  • Figure BDA0005114641050000081
    Figure BDA0005114641050000081
Patent Text Reader

Abstract

The invention discloses a negative plate, a lithium ion battery and electric equipment. The negative plate comprises a negative current collector layer which is arranged in sequence; a first negative electrode active material layer including silicon carbon, first graphite, and first hard carbon; a second negative electrode active material layer including second graphite and second hard carbon; the median diameter of the first graphite is 12-15 [mu] m, and the median diameter of the second graphite is 3-10 [mu] m. Hard carbon at the bottom layer is fully combined with silicon carbon, so that the silicon carbon volume expansion problem can be inhibited, and the overall compaction and low-temperature performance is improved; the hard carbon on the surface layer is combined with the fast-charging graphite, and the large interlayer spacing and isotropic structure of the hard carbon can effectively shorten the lithium ion transmission path, improve the surface layer dynamics and improve the problem of lithium precipitation at the corner of the battery cell. Through the combination of the first negative electrode active material layer and the second negative electrode active material layer, corner lithium precipitation caused by insufficient dynamics is remarkably improved while the high energy density of the silicon-carbon material is fully exerted, and the problem of battery cell rebound expansion under a high-silicon system can be remarkably inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of lithium-ion batteries, and in particular to negative electrode sheets, lithium-ion batteries and electrical equipment. Background Art

[0002] While lithium-ion batteries are widely used, they are also subject to increasingly higher requirements from consumers, such as high energy density, high charging speed, and long battery life. As the market's requirements for energy density become higher and higher, silicon-carbon negative electrode materials with high gram capacity are popular and become the mainstream trend of development. However, silicon-carbon batteries also face the disadvantages of large volume expansion rate, poor low-temperature performance, and severe lithium deposition in corners. How to suppress the expansion of silicon-carbon materials during the cycle process has become a top priority.

[0003] The current mainstream method usually adopts double-layer coating technology, which mixes silicon-carbon materials with high-ED graphite and coats them on the bottom layer, and coats the surface with fast-charging graphite materials. This method can suppress the expansion of silicon-carbon to a certain extent, while ensuring the fast-charging performance of the battery system. However, studies have found that this also inevitably leads to serious corner lithium deposition problems. Therefore, it is necessary to improve the problem of lithium deposition in the corners of the battery cell on the basis of improving the energy density and fast charging of the battery cell. Summary of the invention

[0004] The present application aims to solve at least one of the technical problems existing in the prior art. To this end, the present application proposes a negative electrode sheet and an electrical device.

[0005] In a first aspect of the present application, a negative electrode sheet is provided, the negative electrode sheet comprising:

[0006] Anode current collector layer;

[0007] A first negative electrode active material layer, wherein the first negative electrode active material in the first negative electrode active material layer includes silicon carbon, first graphite and first hard carbon;

[0008] A second negative electrode active material layer, wherein the second negative electrode active material in the second negative electrode active material layer includes a second graphite and a second hard carbon;

[0009] Among them, the median particle size D of the first graphite 1 50 is 12μm to 15μm, and the median particle size D of the second graphite 3 50 is 3μm~10μm.

[0010] The negative electrode sheet according to the first aspect of the present application has the following beneficial effects:

[0011] The negative electrode sheet of the present application forms two active material layers on the negative electrode current collector. The composition of the bottom first negative electrode active material layer close to the negative electrode current collector includes silicon carbon, a first graphite with high ED and a first hard carbon, and the composition of the surface second negative electrode active material layer includes a second graphite with good fast charging performance and a second hard carbon. The bottom hard carbon is fully combined with silicon carbon, which can significantly suppress the volume expansion problem of silicon carbon and improve the overall compaction and low temperature performance; the surface hard carbon is combined with the fast-charging graphite, and the large interlayer spacing and isotropic structure of the hard carbon can effectively shorten the lithium ion transmission path, improve the surface dynamics, and improve the problem of lithium deposition in the corners of the battery cell. Therefore, through the combination of the above-mentioned first negative electrode active material layer and the second negative electrode active material layer, while ensuring that the high energy density of the silicon-carbon material is fully utilized, the corner lithium deposition caused by insufficient dynamics is significantly improved. More importantly, it can significantly suppress the rebound expansion problem of the battery cell under the high silicon system. Specifically:

[0012] (1) The interlayer spacing of hard carbon (e.g. 0.380nm) is larger than that of graphite (e.g. 0.335nm), which is conducive to the rapid embedding and extraction of lithium ions. At the same time, hard carbon has an isotropic structure, and lithium ions can be embedded from all directions at the same time, which is conducive to accelerating the efficiency of lithium embedding. Therefore, the surface mixed with hard carbon can make up for the defect of the long migration distance of lithium ions in the double-layer coating surface and improve the kinetics.

[0013] (2) Silicon carbon has a high gram capacity and is usually mixed with graphite. However, the volume expansion effect of silicon carbon itself makes the battery cell prone to failure during cycling. Hard carbon materials have more voids and a larger specific surface area. Mixing with silicon carbon can provide more space for stress release, thereby suppressing its cyclic expansion problem. At the same time, the voids in hard carbon can effectively store electrolyte, which is beneficial to improving the battery cell's ability to retain electrolyte under high-pressure and dense systems.

[0014] (3) Hard carbon itself has a low compaction. By introducing high-compacted graphite into the bottom layer and adjusting the content and median particle size ratio of the bottom layer graphite to hard carbon, it is possible to ensure the compaction of the bottom layer without losing energy density, while also allowing the bottom layer to exert the high dynamic performance of hard carbon and improve the overall charging capacity of the battery cell.

[0015] In some embodiments of the present application, the mass ratio w2 of the first hard carbon in the first negative electrode active material is 2.5-10%, for example, 2.5%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, or 10%.

[0016] In some embodiments of the present application, the mass ratio w4 of the second hard carbon in the second negative electrode active material is 2.5-7.5%, for example, it can be 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, or 7.5%.

[0017] In some embodiments of the present application, the mass ratio w1 of the first graphite in the first negative electrode active material is 70-92.5%, for example, it can be 70%, 72%, 74%, 75%, 76%, 78%, 80%, 82%, 84%, 85%, 86%, 88%, 90%, 92%, or 92.5%.

[0018] In some embodiments of the present application, the mass ratio w5 of silicon and carbon in the first negative electrode active material is 5-20%, for example, it can be 5%, 6%, 8%, 10%, 12%, 14%, 15%, 16%, 18%, or 20%.

[0019] In some embodiments of the present application, the mass ratio w3 of the second graphite in the second negative electrode active material is 92.5-97.5%, for example, it can be 92.5%, 93%, 93.5%, 94%, 94.5%, 95%, 95.5%, 96%, 96.5%, 97%, or 97.5%.

[0020] In some embodiments of the present application, the median particle size D of the first hard carbon is 2 50 is 3 μm to 5 μm, for example, 3 μm, 4 μm, or 5 μm.

[0021] In some embodiments of the present application, the median particle size D of silicon carbon 5 50 is 6 μm to 10 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, and 10 μm.

[0022] In some embodiments of the present application, the median particle size D of the second hard carbon is 4 50 is 3 μm to 5 μm, for example, 3 μm, 4 μm, or 5 μm.

[0023] In some embodiments of the present application, the first negative electrode active material layer satisfies 0.56≤(D 1 50×w1+D 2 50×w2) / (D 1 50+D 2 50)≤0.71.

[0024] In some embodiments of the present application, the second negative electrode active material layer satisfies 0.44≤(D 3 50×w3+D 4 50×w4) / (D 3 50+D 4 50)≤0.7.

[0025] In some embodiments of the present application, the second negative electrode active material layer and the first negative electrode active material layer satisfy 0.06≤(D 4 50×w4+D 550×w5) / (D 5 50+D 4 50)≤0.22. The hard carbon content in the second negative electrode active material layer is also related to the silicon carbon in the first negative electrode active material layer. When the silicon carbon content is higher, the hard carbon content in the first negative electrode active material layer is also higher to inhibit its expansion. However, in order to ensure the charging capacity of the battery cell, the hard carbon content in the second negative electrode active material layer needs to be reduced. When the above relationship is met, good charging capacity and low expansion can be taken into account at the same time.

[0026] By adjusting the median particle size and mass ratio of the different active materials in the first negative electrode active material layer and the second negative electrode active material layer, the prepared negative electrode sheet can ensure high gram capacity while having excellent kinetic performance, significantly improving the problem of lithium deposition in the corner of the battery cell. Most importantly, a breakthrough has been made in the problem of cyclic expansion of silicon-based battery cells.

[0027] In some embodiments of the present application, the mass ratio of the first negative electrode active material layer to the second negative electrode active material layer is 9:1 to 1:9, for example, it can be 9:1, 8:1, 7:1, 6:1, 5:1, 4:1, 3:1, 2:1, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, or 1:9.

[0028] In some embodiments of the present application, the specific surface area S of the first hard carbon and the specific surface area S of the second hard carbon are independently 6 to 15 m 2 / g, for example, it can be 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g. Generally speaking, the smaller the particle size, the larger the specific surface area, which can effectively release the stress of silicon expansion.

[0029] In some embodiments of the present application, the raw materials of the first negative electrode active material layer and / or the second negative electrode active material layer further include at least one of a conductive agent and a binder. The conductive agent includes but is not limited to conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT) and graphene, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinyl alcohol, polyvinyl butyral, etc.

[0030] In some embodiments of the present application, the first (second) negative electrode active material layer includes 70-99 wt % of the first (second) negative electrode active material, 0.5-6 wt % of the conductive agent and 0.5-20 wt % of the binder.

[0031] In some embodiments of the present application, when the first (second) negative electrode active material, conductive agent and binder are made into a negative electrode sheet, the first negative electrode active material, conductive agent and binder are dispersed in a solvent and then coated on the negative electrode collector, dried, and then the second negative electrode active material, conductive agent and binder are dispersed in a solvent and then continued to be coated and dried to obtain a negative electrode sheet.

[0032] The embodiment of the present application also provides a method for preparing a negative electrode sheet, the method comprising the following steps:

[0033] Coating a slurry of a first negative electrode active material on a current collector to form a semi-finished negative electrode sheet;

[0034] The slurry of the second negative electrode active material is continuously coated on the semi-finished negative electrode sheet to form a finished negative electrode sheet.

[0035] In a second aspect of the present application, a lithium-ion battery is provided. The lithium-ion battery comprises the aforementioned negative electrode sheet.

[0036] In some embodiments of the present application, the lithium-ion battery comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The positive electrode sheet, the negative electrode sheet and the separator are wound to obtain a battery cell and a lithium-ion battery.

[0037] In some embodiments, the positive electrode sheet includes a positive electrode current collector layer and a positive electrode active material layer.

[0038] In some embodiments, the positive electrode current collector layer and the negative electrode current collector layer are independently selected from at least one of metal materials including metal foil (such as aluminum foil, silver foil, tin foil, iron foil, titanium foil, nickel foil, copper foil or alloy foil of the above metals), metal mesh (such as aluminum mesh, silver mesh, tin mesh, iron mesh, titanium mesh, nickel mesh, copper mesh or alloy mesh of the above metals).

[0039] In some embodiments, the positive electrode current collector layer is aluminum foil, and the negative electrode current collector layer is copper foil.

[0040] In some embodiments, the positive electrode active material layer includes a positive electrode active material, which is at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium nickel manganese aluminum oxide.

[0041] In some embodiments, the raw material of the positive electrode active material layer also includes at least one of a conductive agent and a binder. The conductive agent includes but is not limited to conductive graphite (such as KS-6, KS-15, SFG-6, SFG-15, SO, etc.), conductive carbon black (such as Super P, Super S, 350G, acetylene black, Ketjen black, etc.), conductive carbon fiber (such as VGCF, CNT) and graphene, etc. The binder includes but is not limited to at least one of polyvinylidene fluoride, polytetrafluoroethylene, carboxymethyl cellulose, styrene-butadiene rubber, polyurethane, polyvinyl alcohol, polyvinyl butyral, etc.

[0042] In some embodiments, the positive electrode active material layer includes 70 to 99 wt % of the positive electrode active material, 0.5 to 6 wt % of the conductive agent, and 0.5 to 20 wt % of the binder.

[0043] In some of the embodiments, the electrolyte may be at least one of a solid electrolyte or an electrolyte solution.

[0044] In some of the embodiments, the electrolyte includes an electrolyte salt and an organic solvent, wherein the specific types and compositions of the electrolyte salt and the organic solvent are not subject to specific restrictions, and include positive electrode film-forming additives, negative electrode film-forming additives, and cycle-improving and low-temperature additives, etc.

[0045] In some embodiments, the diaphragm includes but is not limited to one polymer or a composite of multiple polymer materials such as polyethylene (PE), polypropylene (PP), polyvinylidene fluoride (PVDF), etc. In some embodiments, the diaphragm also includes a coating (such as ceramic) covering the polymer material.

[0046] In a fourth aspect of the present application, an electrical device is provided, the electrical device comprising the aforementioned lithium-ion battery.

[0047] Among them, electrical equipment refers to any equipment that can use electrical energy and convert it into mechanical energy, thermal energy, light energy or other one or more forms of energy, such as electric motors, electric heat engines, electric light sources, etc. Among them, mobile devices, electric vehicles, electric trains, ships and satellites, energy storage systems, etc. Mobile devices can be mobile phones, laptops, drones, sweeping robots, electronic cigarettes, etc.; electric vehicles can be pure electric vehicles, hybrid electric vehicles, plug-in hybrid electric vehicles, electric bicycles, electric scooters, electric golf carts, electric trucks, etc.

[0048] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. DETAILED DESCRIPTION

[0049] The following will clearly and completely describe the concept of the present application and the technical effects produced in combination with the embodiments, so as to fully understand the purpose, features and effects of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of them. Based on the embodiments of the present application, other embodiments obtained by those skilled in the art without creative work are all within the scope of protection of the present application.

[0050] The embodiments of the present application are described in detail below. The described embodiments are exemplary and are only used to explain the present application, and should not be understood as limiting the present application.

[0051] In the description of this application, "several" means more than one, "many" means more than two, "greater than", "less than", "exceed", etc. are understood to exclude the number itself, "above", "below", "within", etc. are understood to include the number itself, and "about" means within the range of ±20%, 10%, 8%, 5%, 4%, 3%, 2%, 1%, 0.5%, 0.2%, 0.1%, etc. of the number itself. If there is a description of "first" or "second", it is only used for the purpose of distinguishing technical features, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features or implicitly indicating the order of the indicated technical features.

[0052] In the description of the present application, the description with reference to the terms "one embodiment", "some embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.

[0053] The present application is described below in conjunction with specific embodiments.

[0054] Examples 1 to 17

[0055] Embodiments 1 to 17 provide a lithium ion battery, the composition and preparation of each part of which are as follows:

[0056] (1) Positive electrode

[0057] The active material LiCoO2, conductive agent superconducting carbon (Super P), conductive agent carbon nanotubes, and binder polyvinylidene fluoride (PVDF) are fully dispersed and evenly coated on the aluminum foil current collector in an N-methylpyrrolidone solvent system in a mass ratio of 97.6:0.6:0.5:1.3, and then cold-pressed and sliced ​​to obtain the positive electrode sheet.

[0058] (2) Negative electrode

[0059] The negative electrode active material, sodium carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR) and carbon black conductive agent are prepared in a mass ratio of 97.8:0.6:0.6:1 in the slurry of the first negative electrode active material and the slurry of the second negative electrode active material, and mixed with deionized water to form a negative electrode slurry. The two slurries are sequentially coated on the corresponding primer copper foil current collector through a double-layer coating process, dried, and then cold-pressed and sliced ​​to obtain negative electrode sheets.

[0060] (3) Diaphragm

[0061] A ceramic mixture is coated on the surface of the PE film as a diaphragm.

[0062] (4) Electrolyte

[0063] Ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), and propyl propionate (PP) are mixed in a volume ratio of 1:1:4:4, and then fully dried lithium salt LiPF6 is dissolved in a mixed organic solvent at a ratio of 1 mol / L to prepare an electrolyte.

[0064] (5) Full battery preparation

[0065] The above-mentioned positive electrode plate, isolation film and negative electrode plate are made into a bare battery cell, which is then packaged and injected with electrolyte to produce a finished lithium-ion battery.

[0066] The compositions of the first negative electrode active material and the second negative electrode active material in the first negative electrode active material layer and the second negative electrode active material layer are shown in the following table:

[0067] Table 1. Negative electrode composition

[0068]

[0069]

[0070] Furthermore, Comparative Examples 1 to 9 were set with reference to the above-mentioned Examples 1 to 17.

[0071] The performance of the negative electrode sheets and lithium batteries of the embodiments and comparative examples were tested by the following methods:

[0072] (1) Negative electrode sheet half-charge rebound compaction: disassemble the cell after capacity division, take the negative electrode sheet and use a micrometer to measure the thickness. The obtained electrode sheet thickness and current collector thickness are calculated by double-sided coating surface density / (electrode sheet thickness-foil thickness), and the unit is g / cm 3 The greater the rebound density, the smaller the rebound thickness of the negative electrode sheet, and the less energy density the battery cell loses.

[0073] (2) Energy density: calculated according to the following formula: Discharge capacity per cell / (cell width × cell thickness × cell length), unit: Wh / L.

[0074] (3) Cycle retention rate: The battery cell is charged at 2.5C to 4.1V, 2C to 4.2V, 1.5C to 4.3V, and 1C to 4.53V. After 500 cycles, the remaining capacity is the percentage of the initial capacity.

[0075] (4) Cyclic expansion rate: The cell is charged at 2.5C to 4.1V, 2C to 4.2V, 1.5C to 4.3V, and 1C to 4.53V. The difference between the thickness of the cell after 500 cycles and the initial half-charge thickness (i.e., the thickness of the cell at half-charge voltage of 3.9V) is the percentage of the initial half-charge thickness.

[0076] (5) Rate discharge: Fully charge the cell to 4.53 V, and then discharge it at 0.2C to 3.0 V to obtain the initial capacity. After fully charging the cell, discharge it at 2.5C to 3.0 V. The capacity is the percentage of the initial capacity of the cell.

[0077] (6) Corner lithium deposition interface: obtained by disassembling the battery cell after 500 cycles.

[0078] The results are shown in Table 2:

[0079] Table 2. Performance test results of the embodiments and comparative examples

[0080]

[0081] Comparing Example 1 and Comparative Examples 1 to 3, compared with the case where no hard carbon is added to the first negative electrode active material layer and the second negative electrode active material layer, after adding hard carbon to the first negative electrode active material layer or the second negative electrode active material layer, the half-electric rebound compactness of the negative electrode sheet, the energy density of the battery, the room temperature cycle retention rate, and the 2.5C rate discharge all showed a significant improvement, and the expansion rate of 500 cycles at room temperature decreased significantly, and the lithium precipitation situation improved significantly. However, when a certain amount of hard carbon is added to the first negative electrode active material layer and the second negative electrode active material layer at the same time, the half-electric rebound compactness of the negative electrode sheet, the energy density of the battery, the room temperature cycle retention rate, and the 2.5C rate discharge are all much greater than the improvement brought by the addition of both alone and the sum of the increases brought by both, and the decrease in the expansion rate of 500 cycles at room temperature is also the same. The improvement in the lithium precipitation situation is more obvious, and the improvement of the lithium precipitation situation by adding alone is not obvious, and it can only be significantly improved when it is added to the first negative electrode active material layer and the second negative electrode active material layer at the same time.

[0082] Comparing Example 1 and Comparative Example 2, after adding hard carbon to the first negative electrode active material layer, the half-electric rebound compactness of the negative electrode sheet, the energy density of the battery, the room temperature cycle retention rate, and the 2.5C rate discharge are greatly improved, the expansion rate after 500 cycles at room temperature decreases significantly, and the lithium plating situation is significantly improved.

[0083] Comparing Example 1 with Comparative Examples 4 to 5, when the median particle size of the graphite in the first active material layer is too small or too large, (D 1 50×w1+D 2 50×w2) / (D 1 50+D 2 50) is not in the range of 0.56 to 0.71, the energy density and room temperature cycle retention rate of the battery are reduced to varying degrees, and the lithium plating situation is deteriorated.

[0084] Comparing Example 1 with Comparative Examples 6 to 7, when the median particle size of the graphite in the first active material layer is too small or too large, that is, (D 3 50×w3+D 4 50×w4) / (D 3 50+D 4 50) is not within the range of 0.44 to 0.7, the energy density and room temperature cycle retention rate of the battery are reduced to varying degrees, and the lithium plating situation is deteriorated.

[0085] Comparing Example 1 with Comparative Examples 8 to 9, when the silicon carbon content in the first active material layer is too little or too much, that is, (D 4 50×w4+D 5 50×w5) / (D 5 50+D 4 50) is not between 0.06 and 0.22 or (D1 50×w1+D 2 50×w2) / (D 1 50+D 2 50) is not within the range of 0.56 to 0.71, the energy density, room temperature cycle retention rate and lithium deposition at the negative electrode corner of the battery are affected to varying degrees.

[0086] Comparing Examples 1 to 3, with the increase of the hard carbon content in the first negative electrode active material layer, the half-electric rebound compaction and 2.5C rate discharge of the negative electrode sheet gradually increased, and the energy density and room temperature cycle of the battery first increased and then decreased. It was mainly because the addition of hard carbon led to the loss of capacity, while the expansion rate of 500 cycles at room temperature gradually decreased, and the lithium plating situation gradually improved.

[0087] Comparing Examples 1, 4, and 5, as the hard carbon content in the second negative electrode active material layer increases, the half-electric rebound compactness of the negative electrode sheet, the energy density of the battery, and the room temperature cycle retention first increase and then decrease, the expansion of the room temperature cycle for 500 cycles first decreases and then increases, the 2.5C rate discharge gradually increases, and the lithium precipitation situation gradually improves. The hard carbon content of 5% in Example 1 is the best.

[0088] Comparing Examples 1, 6, and 7, with the increase of the silicon-carbon content in the first negative electrode active material layer, the half-electric rebound compactness of the negative electrode sheet gradually decreases, the energy density of the battery first increases and then decreases, the room temperature cycle retention rate gradually decreases, the expansion rate of 500 cycles at room temperature gradually increases, the 2.5C rate discharge gradually decreases, and the lithium plating situation gradually worsens.

[0089] Comparing Examples 1, 8, and 9, as the median particle size of silicon carbon in the first negative electrode active material layer gradually increases, the half-electric rebound density of the negative electrode sheet gradually decreases, the energy density and room temperature cycle retention of the battery first increase and then decrease, the expansion of 500 cycles of room temperature cycle first decreases and then increases, and the 2.5C rate discharge gradually decreases.

[0090] Comparing Examples 1, 10, and 11, as the median particle size of graphite in the first negative electrode active material layer gradually increases, the half-electric rebound density of the negative electrode sheet gradually decreases, the energy density and room temperature cycle retention of the battery first increase and then decrease, the expansion of 500 cycles of room temperature cycle first decreases and then increases, the 2.5C rate discharge gradually decreases, and the lithium plating situation gradually improves.

[0091] Comparing Examples 1, 12, and 13, as the median particle size of the hard carbon in the first negative electrode active material layer gradually increases, the half-electric rebound compactness of the negative electrode sheet, the energy density of the battery, and the room temperature cycle retention first increase and then decrease, the expansion after 500 cycles of room temperature cycling first decreases and then increases, the 2.5C rate discharge gradually decreases, and the lithium plating situation gradually improves.

[0092] Comparing Examples 1, 14, and 15, as the median particle size of graphite in the second negative electrode active material layer gradually increases, the half-electric rebound compactness of the negative electrode sheet, the energy density of the battery, the room temperature cycle retention rate, and the 2.5C rate discharge first increase and then decrease, and the expansion after 500 cycles at room temperature first decreases and then increases, and the lithium precipitation situation is good.

[0093] Comparing Examples 1, 16, and 17, as the median particle size of the hard carbon in the second negative electrode active material layer gradually increases, the half-electric rebound density of the negative electrode sheet gradually decreases, the energy density and room temperature cycle retention of the battery first increase and then decrease, the expansion rate of 500 cycles at room temperature gradually increases, the 2.5C rate discharge gradually decreases, and the lithium plating situation deteriorates.

[0094] Based on the above results, when the first active material layer of the prepared negative electrode sheet satisfies: 0.56≤(D 1 50×w1+D 2 50×w2) / (D 1 50+D 2 50)≤0.71; the layer of the second active material satisfies: 0.44≤(D 3 50×w3+D 4 50×w4) / (D 3 50+D 4 50)≤0.7; and also meet: 0.06≤(D 4 50×w4+D 5 50×w5) / (D 5 50+D 4 50)≤0.22, the prepared battery cell has the best energy density, cycle retention rate, cycle expansion rate and lithium deposition interface.

[0095] The present application is described in detail above in conjunction with the embodiments, but the present application is not limited to the above embodiments, and various changes can be made within the knowledge of ordinary technicians in the relevant technical field without departing from the purpose of the present application. In addition, the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.

Claims

1. A negative electrode sheet, characterized in that: The negative electrode sheet includes: Anode current collector layer; The first negative electrode active material layer, the first negative electrode active material in the first negative electrode active material layer comprises silicon carbon, first graphite and first hard carbon, the median particle size D of the first graphite is 1 50: 12μm~15μm; The second negative electrode active material layer, the second negative electrode active material in the second negative electrode active material layer includes a second graphite and a second hard carbon, and the median particle size D of the second graphite is 3 50 is 6μm~10μm.

2. The negative electrode sheet according to claim 1, characterized in that: The mass ratio w2 of the first hard carbon in the first negative electrode active material is 2.5-10%; and / or the mass ratio w4 of the second hard carbon in the second negative electrode active material is 2.5-7.5%; Optionally, the mass ratio w1 of the first graphite in the first negative electrode active material is 70-92.5%; Optionally, the mass ratio w5 of the silicon-carbon in the first negative electrode active material is 5 to 20%; Optionally, a mass ratio w3 of the second graphite in the second negative electrode active material is 92.5-97.5%.

3. The negative electrode sheet according to claim 2, characterized in that: The median particle size D of the first hard carbon 2 50 is 3 μm to 5 μm; the median particle size D of the silicon carbon 5 50 is 6 μm to 10 μm; the median particle size D of the second hard carbon 4 50 is 3μm~5μm.

4. The negative electrode sheet according to claim 3, characterized in that: The first negative electrode active material layer satisfies 0.56≤(D 1 50×w1+D 2 50×w2) / (D 1 50+D 2 50)≤0.

71.

5. The negative electrode sheet according to claim 3, characterized in that: The second negative electrode active material layer satisfies 0.44≤(D 3 50×w3+D 4 50×w4) / (D 3 50+D 4 50)≤0.

7.

6. The negative electrode sheet according to claim 3, characterized in that: The second negative electrode active material layer and the first negative electrode active material layer satisfy 0.06≤(D 4 50×w4+D 5 50×w5) / (D 5 50+D 4 50)≤0.

22.

7. The negative electrode sheet according to claim 1, characterized in that: The mass ratio of the first negative electrode active material layer to the second negative electrode active material layer is 9:1 to 1:

9.

8. The negative electrode sheet according to claim 1, characterized in that: The specific surface area S of the first hard carbon and the specific surface area S of the second hard carbon are independently 6 to 15 m 2 / g.

9. A lithium-ion battery, characterized in that A negative electrode sheet comprising any one of claims 1 to 8.

10. Electrical equipment, characterized in that: The negative electrode sheet comprises the negative electrode sheet according to any one of claims 1 to 8, or the lithium ion battery according to claim 9.

Citation Information

Patent Citations

  • Negative pole piece, electrochemical device and electronic equipment

    CN114824165A

  • Negative active material, negative pole piece, lithium ion battery and electronic device

    CN116895760A

  • Negative electrode active material, negative electrode slurry, preparation methods of negative electrode active material and negative electrode slurry, negative electrode plate, lithium ion battery and charging method of lithium ion battery

    CN117810449A

  • Negative pole piece, preparation method thereof and electrochemical device

    CN118039789A

  • Designable fast-charging type negative plate

    CN118431408A